The Effect of Work Motivation on Career Development and Compensation on Employee Performance Through Job Satisfaction As Mediation Variables - Marina Marina; Ahmad Badawy Saluy; Novawiguna Kemalasari (Greenation International Journal of Tourism and Management, 2023)
This study aims to analyze the factors that influence employee performance, including Work Motivation, Career Development, Compensation and Job Satisfaction. This study also wants to analyze the effect of work motivation, career development, and compensation on job satisfaction and analyze how job satisfaction mediates the influence of work motivation, career development, and compensation on employee performance. This study used a quantitative approach through questionnaires to 162 respondents with a Likert scale with analysis using SEM-PLS (Structural Equation Modeling-Partial Least Square). Based on the analysis in this study, the results were obtained that: 1) Work motivation has a positive and significant effect on employee performance; 2) Career development has a positive and significant effect on employee performance; 3) Compensation has no significant effect on employee performance; 4) Job satisfaction has no significant effect on employee performance; 5) Work motivation has a positive and significant effect on job satisfaction; 6) Career development has a positive and significant effect on job satisfaction; 7) Compensation has a positive and significant effect on job satisfaction; 8) Job satisfaction does not mediate the effect of work motivation on employee performance; 9) Job satisfaction does not mediate the effect of career development on employee performance; 10) Job satisfaction does not mediate the effect of compensation on employee performance.